DISIPLIN KERJA MEMEDIASI PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA BINTANG SUPER MARKET UBUD GIANYAR - Ni Komang Ari Sastra Yani; Putu Agus Eka Rismawan; Ary Wira Andika (VALUES, 2023)
This study aims to determine the role of work discipline in mediating the effect of work motivation and work environment on employee performance at Bintang Super Market Ubud Gianyar. The research sample is the employees of Bintang Super Market Ubud Gianyar, totaling 40 people who are determined by census. The collected data were analyzed with SmartPLS 3.0. The results of the analysis show that; 1. Work motivation has a positive and significant effect on employee performance at Bintang Super Market Ubud Gianyar. 2. The work environment has a positive and significant effect on employee performance at Bintang Super Market Ubud Gianyar. 3. Work motivation has a positive and significant effect on work discipline at Bintang Super Market Ubud Gianyar. 4. The work environment has a positive and significant effect on work discipline at Bintang Super Market Ubud Gianyar. 5. Work discipline has a positive and significant effect on employee performance at Bintang Super Market Ubud Gianyar. 6. Work motivation has a positive and significant effect on employee performance through work discipline at Bintang Super Market Ubud Gianyar. 7. The work environment has a positive and significant effect on employee performance through work discipline at Bintang Super Market Ubud Gianyar.